Design And Control of an Articulated Robotic Arm for Archery - Khairudin A.R.M.; Baharuddin Z.; Mohamed H.; Hafidz M.H.A.; Keith C.T.J.; Faudzi A.A.M.; Hamid W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Grippers; Hough transforms; Intelligent robots; Robot vision; Signal detection; Archery; Articulated robotics; Design and control; Detection algorithm; Education industry; Machine-vision; Medical areas; Sports area; Targeting Systems; WebCams; Robotic arms